2023
DOI: 10.1155/2023/5591059
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Constituents of Adansonia digitata L. (Baobab) Fruit Pulp from Tekeze Valley, Tigrai, Ethiopia

Abebe Asmamaw Wasihun,
Desta Berhe Sbhatu,
Goitom Gebreyohannes Berhe
et al.

Abstract: Baobab (Adansonia digitata L) is a large tree species growing in semiarid and arid lowlands of Ethiopia and other places. The plant is valued by natives for its contributions as a cash crop and livelihood tree. Previous studies using samples from different countries have documented their phytochemical profiles and nutritional and health benefits. This study explored the phytochemical constituents and biological activities of fruit pulp extracts of baobab collected from Tekeze Valley, Tigrai, Ethiopia. To this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(91 reference statements)
0
0
1
Order By: Relevance
“…Our study has demonstrated that, on average, the total flavonoid concentration is always lower than the total phenolic concentration. These results contradict those reported by Ismail et al [5] and Wasihun et al [48], which reported higher amounts of flavonoids in most of the baobab pulp extracts. However, our results are in accordance with other studies [15,45].…”
Section: Bioactive Compounds and Antioxidant Activitycontrasting
confidence: 96%
“…Our study has demonstrated that, on average, the total flavonoid concentration is always lower than the total phenolic concentration. These results contradict those reported by Ismail et al [5] and Wasihun et al [48], which reported higher amounts of flavonoids in most of the baobab pulp extracts. However, our results are in accordance with other studies [15,45].…”
Section: Bioactive Compounds and Antioxidant Activitycontrasting
confidence: 96%